Anastomosis Groups and Mycovirome of Rhizoctonia Isolates Causing Sugar Beet Root and Crown Rot and Their Sensitivity to Flutolanil, Thifluzamide, and Pencycuron - Can Zhao; Siwei Li; Zhihao Ma; Wenjun Wang; Lihong Gao; Chenggui Han; Anpei Yang; Xuehong Wu (Journal of Fungi, 2023)
Anastomosis groups (AGs) or subgroups of 244 Rhizoctonia isolates recovered from sugar beet roots with symptoms of root and crown rot were characterized to be AG-A, AG-K, AG-2-2IIIB, AG-2-2IV, AG-3 PT, AG-4HGI, AG-4HGII, and AG-4HGIII, with AG-4HGI (108 isolates, 44.26%) and AG-2-2IIIB (107 isolates, 43.85%) being predominate. Four unclassified mycoviruses and one hundred and one putative mycoviruses belonging to six families, namely Mitoviridae (60.00%), Narnaviridae (18.10%), Partitiviridae (7.62%), Benyviridae (4.76%), Hypoviridae (3.81%), and Botourmiaviridae (1.90%), were found to be present in these 244 Rhizoctonia isolates, most of which (88.57%) contained positive single-stranded RNA genome. The 244 Rhizoctonia isolates were all sensitive to flutolanil and thifluzamide, with average median effective concentration (EC50) value of 0.3199 ± 0.0149 μg·mL−1 and 0.1081 ± 0.0044 μg·mL−1, respectively. Among the 244 isolates, except for 20 Rhizoctonia isolates (seven isolates of AG-A and AG-K, one isolate of AG-4HGI, and 12 isolates of AG-4HGII), 117 isolates of AG-2-2IIIB, AG-2-2IV, AG-3 PT, and AG-4HGIII, 107 isolates of AG-4HGI, and six isolates of AG-4HGII were sensitive to pencycuron, with average EC50 value of 0.0339 ± 0.0012 μg·mL−1. Correlation index (ρ) of cross-resistance level between flutolanil and thifluzamide, flutolanil and pencycuron, and thifluzamide and pencycuron was 0.398, 0.315, and 0.125, respectively. This is the first detailed study on AG identification, mycovirome analysis, and sensitivity to flutolanil, thifluzamide, and pencycuron of Rhizoctonia isolates associated with sugar beet root and crown rot.